The relationship between small pelagic fish catches with sea surface temperature and chlorophyll in Makassar Strait waters - Rini Sahni Putri; Hasrianti Hasrianti; Damis Damis; Muhammad Bibin; Andi Rani Sahni Putri; Muh Kasim; Suhartono Nurdin (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2022)
Makassar Strait is a waters area with a large and relatively fertile water resource potential. The Makassar Strait area represents the confluence zone between the Pacific Ocean and Indian Ocean fish populations. The fertility of the waters makes this area one of the breeding zones for most aquatic biota. This study aims to map the catch of small pelagic fishes with water conditions in the Makassar Strait. The data used in this study was fish catches data from Makassar Strait waters from June to September 2021. Data on environmental conditions in the form of Sea Surface Temperature and chlorophyll-a concentration in the waters during the study period were obtained from the AQUA satellite with MODIS sensors, then combined with the Geographic Information System (GIS). The results of this study indicate that the sea surface temperature range in Makassar Strait waters was between 26.7°C–31.3°C and the concentration of chlorophyll-a was between 0.7 mg/m³ - 1.30 mg/m³. The highest catch points were at two points with the same catch of the purse seine, namely 4,000 kg at 118°51'E and 5°10'59